Der „geschliffene" Diamant - Borkowski, Maciej (Studia Germanica Posnaniensia, 2018)
The article is an excerpt from the Ph. D. dissertation entitled „Die Rezeption Friedrich Hebbels im Dritten Reich“ (The reception of Friedrich Hebbel in the Third Reich). The subject of analysis is the Nazi reception of the drama „Der Diamant“ (The diamond) which was transposed from the comedy of human foibles into an anti-Semitic tendentious play in the period of the Third Reich. After confronting the Nazi updating with the author's intentions and interpretations based on the analysis of the text of drama the author reconstructed on the basis of the preserved scripts of the play and theatrical reviews manipulations of the theatres and theatrical criticism aiming at ideological-political functioning of the drama.